Effect of Trichoderma reesei Degraded Date Pits Supplementation on Growth Performance, Immunoglobulin Levels, and Intestinal Barrier Functions of Broiler Chickens - Alyileili, Salem R.; El-Tarabily, Khaled; Ibrahim, Wissam Hachem; Sulaiman, Mohsin; Hussein, Ahmed Soliman (Recent Patents on Food, Nutrition & Agriculture, 2020)
Background: Date palm (Phoenix dactylifera L.) is a dominant fruit crop in most Arabian countries. Date pits, as a major byproduct which remained after consumption of date flesh, proved to be a valuable source of energy. Objectives: The impact of degraded date pits (DDP) on growth performance, intestinal bacterial population, and expression profiles of intestinal genes in broilers was determined. Recent patents have been established on DDP from the European patent office (EP2586318B1), Hong Kong patent registry office (HK1184642) and by the United States patent and trademark office (US8968729B2 and US10265368B2). Methods: Solid-state degradation system (SSD) was used for the preparation of DDP using Trichoderma reesei. One-day-old Brazilian broiler chicks “Cobb 500” were randomly divided into six treatments with six replicates, which consisted of a normal diet containing only corn-soy (control), diet containing corn-soy + (20%, 50g/100Kg oxytetracycline), diet containing corn-soy + 10% (DDP), diet containing corn-soy + 0.2% mannan oligosaccharides (MOS), diet containing corn-soy + 0.1% mannose, and diet containing corn-soy + 0.2% mannose. Results: There were no significant differences in body weight, feed intake, and feed conversion ratio (FCR) in broilers among the treatments. The bacterial count was significantly decreased in 10% DDP diet-fed broilers, 0.2% MOS and antibiotic diet-fed broilers. Immunoglobulin levels in serum and intestinal contents and expression pattern of genes in jejunum were upregulated in 10% DDP and 0.2% MOS diet-fed broilers. Conclusion: DDP can be used as an energy source for replacing part of corn, mannan oligosaccharide and also recommended as a potential alternative to antimicrobials in broilers diet.
Keywords: immunoglobulin